Karyotypes of Some Ghanaian Shield-Bugs and the Higher Systematics of Pentatomoidea (Hemiptera:Heteroptera) - Nuamah, K.A. (University of Ghana, 1980)
Data on 2n-numbers of some fifty-five (55) species, belonging to six families of some Ghanaian shield bugs, collected in Southern Ghana, West Africa are presented. Microphotographs and tracings of karyotypes observed for each species are produced as figures. Histograms of chromosome numbers of the various families have been constructed and these results together with the existing information in literature, is analyzed and discussed. In all two hundred and seventeen (217) species of Pentatomoidea were found to be known cytologically in the literature. With the present work the total number of species of shield-bugs where the Karyotypes is now known stands at two hundred and sixty-six (266). The following karyotype groups appear to emerge from the study; 14 and 12. Under the group 14 is the family Pentatomidae, whilst the families, Scutelleridae, Gydnidae and Plataspidae fall under the karyotype group 12. No basic chromosome number can however be cited for the other families of Pentatomoidea, namely, Dinidoridae, Tessaratomidae, Acanthosomatidae and Urostylidae, because the cytological data for each of these are too scanty, for any such conclusions to be arrived at. The inter-relation of various groups in the superfamily Pentatomoidea are discussed, and the present investigations tend to support the work and conclusions arrived at by morpho-taxonomical studies.